A physiological control system for ECG-synchronized pulsatile pediatric ventricular assist devices. (March 2020) - Cordeiro, Thiago D.; Sousa, Daniel L.; Cestari, Idágene A.; Lima, Antonio M.N.
Highlights: A physiological control system is proposed to keep the mean arterial pressure at a specified reference value. The control system is designed to be used with pulsatile pediatric ventricular assist devices. The control system works in synchronization with the native heartbeat. The controller gains were determined by using the interior-point method to solve a constrained minimization problem. The in silico test results show that the synchronous physiological control system provided a proper cardiovascular response under the different patient level of activities. Abstract: Ventricular assist devices (VADs) are mechanical pumps used to provide support to the circulatory system of patients with ventricular dysfunction that are waiting for heart transplantation. The majority of pulsatile VADs are used in the fill-to-empty mode or the asynchronous mode at a fixed rate. However, when this support lasts for weeks or months, physiological control systems can improve the treatment by changing VAD operation in response to changes in the cardiovascular system. In this work, a physiological control system was developed to adjust the pump ejection pressure at each cardiac cycle to keep the mean arterial pressure at a specified reference value. A polynomial controller was used, and the optimum parameters for this controller were determined by using the interior-point method to solve a constrained minimization problem. A heartbeat detection algorithm based on electrocardiogram signals (ECG) is used in such a way the control system works in synchronization with the physiological heartbeat. Mathematical models of the pediatric cardiovascular system (pCVS) and a pulsatile pediatric pump were used to evaluate the cardiovascular response under ventricular assistance. Computational simulation results were analyzed, and based on them one may conclude that the synchronous physiological control system adapted the cardiovascular response to the changes in references values, defined in accordance with the patient clinical status.